Association between pncA Gene Mutations, Pyrazinamidase Activity, and Pyrazinamide Susceptibility Testing in Mycobacterium tuberculosis - Aono, Akio (American Society for Microbiology, 2014)
We determined MICs for, confirmed the presence of pncA mutations in, and performed pyrazinamidase testing on colonies (subclones) obtained from seven isolates that exhibited differential pyrazinamide (PZA) susceptibility. Six of the seven strains were found to exhibit characteristics resulting from the mixture of strains possessing different properties. In addition, our analysis revealed large pncA-spanning deletions (1,565 bp, 4,475 bp, and 6,258 bp) in three strains that showed high PZA resistance.